Changes Introduced in the Open Reading Frame of Bovine Viral Diarrhea Virus During Serial Infection of Pregnant Swine - Kuca, Thibaud; Passler, Thomas; Newcomer, Benjamin W.; Neill, John D.; Galik, Patricia K.; Riddell, Kay P.; Zhang, Yijing; Bayles, Darrell O.; Walz, Paul H. (Frontiers in Microbiology, 2020)
Bovine viral diarrhea virus (BVDV) is one of the most economically important viruses of cattle, but this pathogen is also able to infect pigs, camelids, and a wide range of domestic and wild ruminants. BVDV isolates circulating in animal populations are genetically and antigenically highly diverse. Acute BVDV infections in cattle cause the introduction of many substitutions in the viral genome. Serial infection of pregnant sheep with a BVDV-1b isolate of bovine origin was also associated with great numbers of substitutions. To our knowledge, genomic changes arising during BVDV infections in swine have not been investigated. The purpose of this study was to investigate the changes occurring in the open reading frame (ORF) of BVDV during serial infection of pregnant swine with a BVDV isolate of bovine origin. The BVDV-1b isolate AU526 was serially passaged in six pregnant gilts, two of which gave birth to live piglets congenitally infected with BVDV. The complete ORF sequences of 14 BVDV isolates obtained from pregnant gilts and their piglets were determined. Their analysis revealed that serial transmission of AU526 in pregnant swine resulted in many genomic changes. All isolates of porcine origin shared 32 nucleotide and 12 amino acid differences with the virus inoculum AU526. These changes were detected after a single passage in pregnant swine and were conserved during the subsequent five passages. Amino acid changes occurred primarily in genomic regions encoding the BVDV structural proteins E2 and Erns. These results suggest that BVDV infections in pregnant swine may contribute significantly to the genetic variability of BVDV and lead to the appearance of adaptive changes.